ANALISIS KEBUTUHAN BAHAN AJAR DIGITAL SEJARAH TERINTEGRASI NILAI-NILAI MULTIKULTURAL PERSAUDARAN SETIA HATI TERATE UNTUK MENINGKATKAN SIKAP TOLERANSI - Abdul Rohman; Sariyatun Sariyatun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This study aims to analyze the need for historical digital learning materials in learning history by integrating the multicultural values of the loyal heart of Pencak silat to increase student tolerance. This study uses a research and development (R & D) method with the ADDIE development model (analysis, design, development, implementation, evaluation) (Aldoobie, 2015). The subjects used as informants at this stage include teachers who teach history subjects in class XI IPS and 30 students in class XI IPS 3. The data collection of this preliminary study is carried out through literature studies, observations and interviews. Data processing uses two types of data analysis, flow analysis (flow analysis models) and interaction analysis (interactive analysis models). The research results show that there are several problems when learning history in the classroom. Firstly, the teaching materials used so far in the form of textbooks and worksheets (student worksheets) are not of maximum value and do not meet the needs of students in the classroom. The learning process is therefore boring and does not interest students. Secondly, the availability of historical teaching materials containing tolerance is still lacking. On this basis, it is necessary to develop additional teaching materials that can support the use of textbooks and worksheets (student worksheets), as well as more effective and innovative teaching materials, adapted to the development of science and technology. The teaching material offered is a digital teaching material integrated with the multicultural values of the Setia Hati Terate fraternity.